The Surface Impedance: A Pertinent Parameter to Describe Finite Conductivity Materials in Numerical Codes - Gobin, V.; Aparicio, J. P.; Grando, J.; Alliot, J. C. (9th International Zurich Symposium and Technical Exhibition on Electromagnetic Compatibility, 1991)
This paper deals with the description of finite conductivity materials in numerical codes solving Maxwell's equations. We show that the surface impedance concept leads to a good representation in many practical cases and numerical results are validated with analytical formulas comparisons. The domain of validity of the surface impedance modeling is finally discussed.